How to avoid being killed in a war zone - Garthwaite, Rosie (aldoha Bloomsbury-(3OGQ HdheRHQjs, 2011)
Whether you're a war correspondent or an aid worker, a tourist worried about an increasingly hostile world or an armchair traveler concerned that your own backyard is fast becoming a war zone, How to Avoid Being Killed in a War Zone will help you survive some of the world's most volatile environments
"The essential survival guide for dangerous places"
12
Keywords: Disaster relief; Disaster; Fireproofing; Safety regulation; Survival skills